Propagation of Sonic Waves in Radiating Gases - Srinivasan S.; Ram R. (My University, 2025)
The paper discusses the propagation of a sonic discontinuity in a radiating gas. The velocity of propagation is determined and it is shown that the velocity of propagation of the sonic discontinuity is not influenced by the radiative heat transfer under thin gas approximation. The fundamental differential equations governing the growth of the sonic discontinuity are obtained and solved. It is concluded that if the sonic discontinuity is a compressive wave of order 1, then it terminates into a shock wave after a critical time tc which has been determined. But on the other hand, if it is an expansion wave of order 1, it will decay and be damped out ultimately. Particular cases of plane and spherical wave fronts have been discussed in details. Copyright © 1977 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim